Development of an Ethnomathematics Module Based on the Pancasila Student Profile in Learning Flat and Solid Geometry - Anisa Fitri; Astrid Chandra Sari (Universitas Pendidikan Mandalika, 2025)
This research aims to develop module with context ethnomathematics wisdom local Bojonegoro on geometry, flat and solid geometric shapes that are valid and practical and have potential effects. This study is a development research using the ADDIE model. The subjects of this study include validators (media experts, material experts), mathematics teachers, and 8th grade students. Data collection techniques were carried out by interviews, filling out questionnaires, and tests. Based on research results, developed modules own validity of 0.82 so that categorized as very valid. The practicality of the module based on teacher responses of 84% is in the very practical category and student responses (small groups) of 97.2% are in the very practical category. Meanwhile , the use of module show positive impact to student learning outcomes of 75.9% are in the good category. Based on these data, the module ethnomathematics based on Pancasila student profile on flat and solid geometry material proven to be very valid, practical, and shows impact positive on student learning outcomes so that worthy used in learning.